2005
DOI: 10.1007/s11010-005-3446-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin-II receptor blocker candesartan cilexetil in rats with dilated cardiomyopathy

Abstract: We examined effects of an angiotensin-II receptor blockers, candesartan cilexetil, in rats with dilated cardiomyopathy after autoimmune myocarditis. Candesartan cilexetil showed angiotensin-II blocking action in a dose-dependent manner in rats with dilated cardiomyopathy. Twenty-eight days after immunization, surviving Lewis rats were divided into four groups and given candesartan cilexetil at 0.05 mg/kg, 0.5 mg/kg or 5 mg/kg per day (Group-C0.05, n = 15, Group-C0.5, n = 15 and Group-C5, n = 15, respectively) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…These results suggest that hypoadiponectinemia is related to myocardial injury in obese mice with acute viral myocarditis. The AT1-receptor blocker reduced cardiac fibrosis, inflammation and increased adiponectin concentrations [15,23,24]. In our study, administration with candesartan significantly increased adiponectin concentrations and decreased severity of myocardial injury associated with the attenuation of cardiac hypertrophy and inflammation in obese mice with acute viral myocarditis.…”
Section: Discussionsupporting
confidence: 60%
“…These results suggest that hypoadiponectinemia is related to myocardial injury in obese mice with acute viral myocarditis. The AT1-receptor blocker reduced cardiac fibrosis, inflammation and increased adiponectin concentrations [15,23,24]. In our study, administration with candesartan significantly increased adiponectin concentrations and decreased severity of myocardial injury associated with the attenuation of cardiac hypertrophy and inflammation in obese mice with acute viral myocarditis.…”
Section: Discussionsupporting
confidence: 60%
“…We have previously reported that candesartan treatment reduced mortality, heart weight (HW), myocardial fibrosis and mRNA expressions of TGF-b1, and improved the survival rate and cardiac function in rats with DCM after myocarditis in a dose-dependent manner. 11 So far, only a few studies have investigated the effects of AT 1 R blockade in experimental myocarditis. 12 It is therefore important to determine the effect of ARBs on fetal gene expression or extracellular matrix (ECM) remodeling in models not only with heart failure after myocardial infarction, but also with DCM.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others have reported that treatment with angiotensin II type1 blockers (ARB) reduces viral-mediated myocardial injury [3,4]. ARB has been shown to have antiinflammatory properties in vitro and animal studies.…”
Section: Introductionmentioning
confidence: 99%